The problems of creating a personal learning environment - T. V. Tarnavskaya (CTE Workshop Proceedings, 2015)
Objectives of the study: analysis of the current stage of the implementation of a personal learning environment. Research objectives is to select own personal learning environment for students. Object of study: a personal learning environment. Research subject: the problems of creating a personal learning environment. Methods: source analysis, definition synthesis. Research results: the creation of a personal learning environment has a number of negative and positive aspects, so this problem requires further research and testing of the results obtained.